Instagram as a Medium for Teaching and Learning English: A Qualitative Systematic Review - Daviq Rizal; Resti Farikhah Z (Universitas Muhammadiyah Jember, 2021)
The purpose of the research paper was to explore the use of Instagram as social media in learning English skills such as reading, speaking, listening, and writing skills. Using a qualitative systematic review, the researchers searched 24 journal articles on the use of Instagram in English language teaching and learning in Google Scholar for data saturation and analysis. This entailed reading and re-reading the manuscripts, followed by coding the data, with each pass enhancing and modifying the codes. The study showed that Instagram could be used as a teaching tool for English language learners and helpful in their English learning. Teachers should use the chance to make the most of this advancement and start using Instagram in the classroom. Because Instagram is one of the most popular social media platforms, students can practice writing about their daily activities and provide feedback on their classmates' writing. According to this study, using Instagram to teach students how to write descriptive writings is beneficial. Furthermore, the experimental students given Instagram media therapy outperformed control students. The results can be significant inputs for English language teachers to use Instagram in real classrooms.